(untitled) (Plant Tissue Culture and Biotechnology, 2012)
The callus tissues of Prosopis cineraria (L.) Druce established and maintained for a period of eight months on MS supplemented with 2 mg/l, 2, 4-D and its plant parts were used for estimation of ascorbic acid. The tissue thus grown was transferred to fresh MS and MS singly supplemented with 0.5, 1, 1.5 and 2% of glucose. The growth indices and ascorbic acid contents in tissues were determined at time interval of two, four, six and eight weeks. Six weeks old tissue cultures showed an increase in the amount of endogenous ascorbic acid as well as growth indices in all the samples. The cultures grown on MS supplemented with 1.5% of glucose showed maximum ascorbic acid content (174.23 mg/100 gdw) and growth index (19.68). Tissues reared with different concentration of glucose showed remarkably high content of ascorbic acid content as compared to control and plant parts. Plant Tissue Cult. & Biotech. 22(1): 27-32, 2012 (June) DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11244